PEMBUATAN KEBUN RUMPUT ODOT (Pennisetum Purpureum cv. Mott) SEBAGAI PAKAN HIJAU TERNAK RUMINANSIA DI DESA URAUR KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Hepirjon Silalahi; Lily Joris; Shirley Fredriksz (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Animal feed forage is the main source of food that is needed the most by ruminant livestock to survive, breed, and increase their productivity. One of the high-quality grass that is most often given to the livestock is bermudagrass (pennisetum purpureum cv. Mott.), because it has a high nutritional content and is palatable. The purpose of community service activity in Uraur village, Kairatu, West Seram Region in the form of education and production of cultivation garden for high quality grass such as bermudagrass (pennisetum purpureum cv. Mott.), is to increase the knowledge of breeders and to provide fresh greed feed with high nutritional value, in order to fulfill the need of ruminant livestock. This community service activity uses the participatory observation method, involving villagers that own livestock in Uraur Village as respondents and partners. This activity increases the knowledge of the breeders because by planting high quality grass (bermudagrass) and using it as fodder they could increase their livestock’s productivity, which in return contribute to the wellbeing of cattle (ruminant livestock) breeders. It most likely happens because bermudagrass has 10 -15 % protein content depending on harvest age, and has low content of crude fiber. The production of bermudagrass could reach up to 60 Ton/Ha/Year. This community service could increase the knowledge about cultivation of high quality grass (bermudagrass), and the availability of sample grass field for breeders in Uraur Village.